Grice's Types of Maxims in "Willoughbhys" Movie - Kristin Enjelina Sidabutar (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2022)
This study aimed to find out the cooperative principle using the types of maxims. The main theory used in this study purposed by Grice (1975) the cooperative principle. And for the research design this study applied the descriptive qualitative as the method. As for collecting the data the researcher applied the theory of observational method and non-participatory technique by (Sudaryanto, 2015). Moreover, in analyzing the data the method of pragmatic identity and the technique pragmatic competence- in equalizing were used in this study. And all of the theories were applied to the movie titled â€œWilloughbysâ€. The findings of this study indicated that the characters in the film adopted four types of maxims they are maxims of quality, maxims of quantity, maxims of relation, and maxims of manner. The maxims of quality showed as the most frequent types, appearing six times. And the quantity maxims occurred four times. The relation maxims occurred four times. Finally, the maxims of manner emerged as the least number of maxims types, with three appearances.Keywords: cooperative principle, maxim, pragmatics